Akseptabilitas Tafsir Indonesia di Pesantren: Studi Multi Kasus di Jember: The Acceptability of Indonesian Qur'anic Exegesis in Islamic Boarding Schools: A Multi-Case Study in Jember - Uun Yusufa (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2014)
The curriculum of Islamic boarding schools (pesantren) has only accepted a few Indonesian translations of Qur'anic exegesis (tafsir), such as Marah Labid by Muhammad Nawawi al-Bantani and al-Ibriz by Bisri Mustofa. The acceptance of Indonesian tafsir does not align with its development in Indonesia. Technically, the pesantren community views Indonesian tafsir merely as translations into Indonesian. However, pragmatically, pesantren still acknowledge and accept Indonesian tafsir as mu'tabar (authoritative) works based on the chain of teachers (sanad), translation quality, and the exegete's competence. On the other hand, the pesantren community also rejects or remains cautious about the emergence of non-mu'tabar tafsir, the increasing number of Qur'anic translations driven by personal desires, and similar issues. Kurikulum pesantren hanya menerima sedikit karya tafsir Al-Qur'an berbahasa Indonesia, seperti Marah Labid karya Muhammad Nawawi al-Bantani dan al-Ibriz karya Bisri Mustofa. Penerimaan tafsir Indonesia ini tidak sebanding dengan perkembangan tafsir di Indonesia. Secara teknis, masyarakat pesantren memandang tafsir Indonesia sekadar terjemahan ke dalam bahasa Indonesia. Namun secara pragmatis, pesantren tetap mengakui dan menerima tafsir Indonesia sebagai karya yang mu'tabar (disepakati) berdasarkan sanad (mata rantai guru), kualitas terjemahan, dan kompetensi penafsir. Di sisi lain, masyarakat pesantren juga menolak atau mewaspadai munculnya tafsir yang tidak mu'tabar, peningkatan jumlah terjemahan Al-Qur'an yang dipengaruhi nafsu, dan sebagainya.